Mapping the Intellectual Structure and Thematic Evolution of Women’s Empowerment Research at the Agriculture Tourism Nexus in Indonesia - Indra Irjani Dewijanti; Putrawan Habibi (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2025)
Research on women’s empowerment at the intersection of agriculture and tourism in Indonesia has expanded across multiple disciplinary domains, yet its intellectual structure and thematic evolution remain unclear. This study maps the knowledge architecture of this interdisciplinary field using bibliometric and science mapping techniques. Drawing on indexed publications retrieved from Scopus and Web of Science, the analysis employs performance indicators, co citation networks, co word clustering, and thematic evolution analysis to identify dominant research streams and emerging trajectories. The findings reveal a fragmented but growing body of scholarship structured around three major clusters: livelihood and rural development, gendered labor and agency, and community based tourism governance. Over time, the field has shifted from descriptive case studies toward more policy oriented and sustainability driven discussions, although theoretical integration remains limited. The study contributes by clarifying intellectual foundations, identifying underexplored intersections, and outlining future research directions for advancing gender responsive development at the agriculture tourism nexus in Indonesia.